Effect of the Modification of Catalysts on the Catalytic Performance - Papa, Florica; Vasile, Anca; Dobrescu, Gianina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue, "Effect of the Modification of Catalysts on the Catalytic Performance", should be of great interest to all researchers involved in this scientific area regarding the synthesis and characterization of various catalysts or catalytic materials; catalytic performance (activity and selectivity); synergetic effect; and the modification of catalysts or suitable promoters that are added to modify the catalyst structure.